Ecofriendly Isolation of Cellulose from Eucalyptus lenceolata: A Novel Approach. (20th December 2018) - Rehman, Noor; Alam, Sultan; Amin, Noor Ul; Mian, Inamullah; Ullah, Hidayat
Abstract : This study reports the extraction of cellulose by means of an environment-friendly multistep procedure involving alkaline treatment and totally chlorine-free bleaching. The multistep process begins with the removal of pectin, cutin, waxes, and other extractives from Eucalyptus lenceolata straw, followed by the removal of hemicelluloses and lignin using an alkaline treatment, and lastly by further delignification of the cellulose pulp through a two-step bleaching process, first with the use of hydrogen peroxide/tetraacetylethylenediamine (TAED) and then with the use of a mixture of acetic and nitric acids. The Eucalyptus lenceolata samples were collected from the mountains of the Malakand division of Khyber Pakhtunkhwa, Pakistan and were ground into smaller particles. The pulp resulting from each step was characterized by infrared spectroscopy (ATR-FTIR) to detect structural changes. The purified cellulose was characterized through different analytical techniques such as Fourier transfer infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM). The isolated cellulose has a high degree of purity and crystallinity (73%) and thermal stability as verified by XRD and TGA, respectively. SEM was used to study the surface morphology of cellulose, indicating that the surface was free from lignin and hemicelluloses due to the chemical treatment. This study indicates that the multistep procedure is quite adequate for the extraction of cellulose.